Analisis Strategi Perencanaan Pembangunan Wilayah melalui Musrenbang di Kabupaten Sumenep - Navilah Ulliyah; Mashur Mashur (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2026)
This study aims to analyze the influence of community participation, institutional capacity, and intergovernmental coordination on the effectiveness of regional development planning through the Development Planning Consultation Forum (Musrenbang) in Sumenep Regency. This research employs a quantitative approach with a descriptive-verificative design. Primary data were collected through questionnaires distributed to Musrenbang participants across 10 purposively selected districts, supported by secondary data from regional planning documents. Data were analyzed using multiple linear regression with statistical software. The results indicate that community participation, institutional capacity, and intergovernmental coordination have a positive and significant effect on the effectiveness of development planning. Institutional capacity emerges as the most dominant factor influencing the quality of Musrenbang outcomes. The model explains 68.4% of the variation in planning effectiveness. These findings highlight the importance of strengthening institutional capacity, enhancing the quality of public participation, and optimizing cross-sectoral coordination to achieve effective and responsive regional development planning.